Is concomitant cholecystectomy with laparoscopic sleeve gastrectomy safe? - Coşkun, Halil; Hasbahçeci, Mustafa; Bozkurt, Süleyman; Çipe, Gökhan; Malya, Fatma Ümit; Memmi, Naim; Karatepe, Oğuzhan; Akçakaya, Adem; Müslümanoğlu, Mahmut (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: To study the effect of selective concomitant cholecystectomy (SCC) on laparoscopic sleeve gastrectomy (LSG). Materials and Methods: A retrospective case-control study of 16 morbidly obese patients treated with concomitant LSG as the primary bariatric surgery and SCC for proven gallbladder (GB) pathology (Group A) between November 2010 and February 2013 was performed. Randomly selected 32 patients who underwent laparoscopic sleeve gastrectomy was the control group (Group B). Results: A total of 48 patients with a mean age of 35.5±10.7 years were included. Demographic data of groups were similar except that there were more female patients in the Group A (p=0.036). Mean body mass index (kg/m2) was 51.1±5.6 and 50.9±5.4 in Groups A and B, respectively (p=0.894). The mean operative time for patients with and without cholecystectomy was 157.2±40 and 95.72±6.2 min, respectively (p=0.001). Cholecystectomy resulted in an additional mean operative time of 49.1±27.9 min without any specific complication. There was no statistical difference with regard to overall morbidity (p=0.316) and the length of hospital stay (p=0.528) between groups. Conclusion: Although an increase in operative time may be an important issue, SCC can be performed on all patients with proven GB pathology during LSG without an increase in morbidity or length of hospital stay.